2016
DOI: 10.1038/srep38546
|View full text |Cite
|
Sign up to set email alerts
|

Decadal shifts of East Asian summer monsoon in a climate model free of explicit GHGs and aerosols

Abstract: The East Asian summer monsoon (EASM) experienced decadal transitions over the past few decades, and the associated "wetter-South-drier-North" shifts in rainfall patterns in China significantly affected the social and economic development in China. Two viewpoints stand out to explain these decadal shifts, regarding the shifts either a result of internal variability of climate system or that of external forcings (e.g. greenhouse gases (GHGs) and anthropogenic aerosols). However, most climate models, for example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 49 publications
(54 reference statements)
5
29
0
Order By: Relevance
“…The spatial pattern of summer winds and precipitation anomalies between the MCA and LIA ( Fig. 2d) further indicate that when southerlies over East Asia reinforce, precipitation over almost all of eastern China increases, consistent with the findings of Liu et al (2011a). In addition, the in-phase changes of the EASM strength and precipitation over eastern China are shown in both the MEM and individual PMIP3 models' results ( Fig.…”
Section: Variations Of Easm and Precipitation Over Eastern China Durisupporting
confidence: 82%
See 1 more Smart Citation
“…The spatial pattern of summer winds and precipitation anomalies between the MCA and LIA ( Fig. 2d) further indicate that when southerlies over East Asia reinforce, precipitation over almost all of eastern China increases, consistent with the findings of Liu et al (2011a). In addition, the in-phase changes of the EASM strength and precipitation over eastern China are shown in both the MEM and individual PMIP3 models' results ( Fig.…”
Section: Variations Of Easm and Precipitation Over Eastern China Durisupporting
confidence: 82%
“…Numerical simulations offer a useful tool to examine climate change and the associated dynamic mechanisms in the past. Based on the ECHO-G simulation, Liu et al (2011a) indicated that the EASM was strengthened and summer precipitation increased over eastern China during the MCA, which were attributed to the increased total solar irradiation. Man et al (2012) indicated that the EASM became stronger during the MCA, but precipitation increased (decreased) in north (south) China in the Max Planck Institute Earth system model (MPI-ESM) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, air–sea interaction is very important to climate simulation in East Asia and western North Pacific region (Wang et al ., ; Zou and Zhou, ; Song and Zhou, ; Lin et al ., ). Thus, besides AMIP‐type simulation, we also examined coupled simulation in 37 CMIP5 models.…”
Section: Resultsmentioning
confidence: 97%
“…Thus in AMIP‐type experiments, warm (cold) local SST will lead to more (less) local precipitation over tropical areas. However, the atmospheric feedback cannot be ignored in WNPSH region (Zou and Zhou, ; Lin et al ., ). Worth noting is that the process explained here applied only to tropical areas.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation